The Use of Watermelon Rind Flour as Stabilizer for Reduced Fat Mayonnaise (Faculty of Animal Science Universitas Brawijaya, 2020)
Reduced fat mayonnaise is a mayonnaise that reduces some oil to reduced fat content, but reduced fat mayonnaise has a disavantages. A decrease in the oil phase which can affect the stability of the mayonnaise emulsion. One alternative is the addition of watermelon rind flour to increase the quality of mayonnaise. The purpose of this study was to determine the quality of mayonnaise with the addition of watermelon rind flour as stabilizer. The method used was experimental design using a completely randomized design. The treatment were the addition of watermelon rind flour as much as 2%, 4%, 6% and control as a comparison. Data were analyzed by analysis of variance and continued with UJBD. The results showed that the addition of watermelon rind flour gave highly significant effect on emulsion stability and moisture content, had a significant effect on pH and did not gave significant effect on sensory evaluation of mayonnaise. This study concluded that the addition of 6% watermelon rind flour as stabilizer produces good quality mayonnaise.